Interaction Characteristic Studies of Ciprofloxacin and/or Sulphadiazine with Bovine Serum Albumin by Spectroscopic Technique - Liu, Xu-Yang; Wang, Qian; Shi, Zhi-Hong; Xia, Xiang-Hua; Sun, Han-Wen (Asian Journal of Chemistry, 2015)
In this paper, the interaction of ciprofloxacin (CPFX) and/or sulphadiazine (SD) with bovine serum albumin (BSA) under simulative physiological conditions was studied, by fluorescence quenching in combination with UV-visible spectroscopic method. The fluorescence quenching constants, binding distance and binding constants for BSA-CPFX and/or sulphadiazine systems were determined. The fluorescence quenching of BSA by addition of ciprofloxacin and/or sulphadiazine is due to static quenching and energy transfer. The binding constants (KA) of BSA-SD and BSA-CPFX systems were 4.04 × 106 and 6.96 × 105 M-1, respectively, showing that sulphadiazine has higher binding capability with bovine serum albumin than ciprofloxacin. In the presence of sulphadiazine or ciprofloxacin, the KA values of BSA-CPFX or BSA-SD systems decreased to 4.63 × 103 or 6.56 × 104 M-1, suggesting that free ciprofloxacin and sulphadiazine in blood increased in their co-presence. Circular dichroism spectra, synchronous fluorescence and three-dimensional fluorescence studies showed that the presence of ciprofloxacin and/or sulphadiazine could change the conformation of bovine serum albumin during the binding process. The results are of great importance in pharmacy, pharmacology and biochemistry.